Muslim Family Digital Literacy and Social Resilience: A Collaborative Governance Model in Facing Digital Era Disruption from the Perspective of Maqashid al-Syari'ah Jamaluddin Athiyyah - Muzayyanah; Iffatin Nur; Dede Nurrahman; Hosaini (International Conference on Humanity Education and Society (ICHES), 2026)
The disruption of the digital era has changed patterns of interaction, communication, and parenting within Muslim families, while simultaneously presenting various challenges to family social resilience, such as exposure to negative information, declining quality of interpersonal communication, and increased vulnerability to domestic conflict. This article aims to analyze the role of Muslim family digital literacy as an instrument for strengthening social resilience through a collaborative governance model from the perspective of Maqashid al-Syari'ah Jamaluddin Athiyyah. This study uses a qualitative approach with a library research method that examines various scientific literature, public policies, and relevant sources related to digital literacy, family resilience, collaborative governance, and Maqashid al-Syari'ah. Data were analyzed using content analysis and critical interpretation techniques. The results show that strengthening Muslim family digital literacy requires multi-stakeholder collaboration involving the government, educational institutions, religious organizations, community groups, and families as the main actors. From the perspective of Maqashid al-Syari’ah Jamaluddin Athiyyah, the collaborative governance model contributes to the protection of religion (hifz al-din), life (hifz al-nafs), reason (hifz al-‘aql), descendants (hifz al-nasl), and property (hifz al-mal). This study confirms that digital literacy based on Islamic values ​​can be an effective strategy in building adaptive, resilient, and competitive Muslim families amidst the dynamics of digital society.